ANALISIS SISTEM PEMBIAYAAN ARRUM (AR-RAHN USAHA MIKRO DAN KECIL) PADA PT. PEGADAIAN CABANG SYARIAH SIMPANG PATAL KOTA PALEMBANG - Elia Trianti; Inten Meutia; Aspahani Aspahani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2013)
The purpose of this research is to know whether the implementation of financing system ARRUM conducted by PT. Simpang Patal Palembang Branch Office is in accordance with the related legal bases, namely Fatwa DSN-MUI No. 25/DSN-MUI/III/2002 and PSAK N 0.107 and Islamic microfinance concept with sharia mortgage and micro-small business. This research is a descriptive study with compare rule or Sharia according to Syariah with current practice of pawn. The sample OF This research is the Sharia Branch Pawnshop Of Simpang Patal Palembang. Based on the results of the analysis can be concluded that the practice of Rahn on the product Ar-Rum pawnshop Sharia is in accordance with the jurisprudence.